Decrease in p3-Alcβ37 and p3-Alcβ40, products of Alcadein β generated by γ-secretase cleavages, in aged monkeys and patients with Alzheimer's disease - Hata, Saori (Alzheimers Dement (N Y), 2019)
INTRODUCTION: Neuronal p3-Alcβ peptides are generated from the precursor protein Alcadein β (Alcβ) through cleavage by α- and γ-secretases of the amyloid β (Aβ) protein precursor (APP). To reveal whether p3-Alcβ is involved in Alzheimer's disease (AD) contributes for the development of novel therapy and/or drug targets. METHODS: We developed new sandwich enzyme-linked immunosorbent assay (sELISA) systems to quantitate levels of p3-Alcβ in the cerebrospinal fluid (CSF). RESULTS: In monkeys, CSF p3-Alcβ decreases with age, and the aging is also accompanied by decreased brain expression of Alcβ. In humans, CSF p3-Alcβ levels decrease to a greater extent in those with AD than in age-matched controls. Subjects carrying presenilin gene mutations show a significantly lower CSF p3-Alcβ level. A cell study with an inverse modulator of γ-secretase remarkably reduces the generation of p3-Alcβ37 while increasing the production of Aβ42. DISCUSSION: Aging decreases the generation of p3-Alcβ, and further significant decrease of p3-Alcβ caused by aberrant γ-secretase activity may accelerate pathogenesis in AD.